Analysis Model of Detection Level of Food-Stood Railway and Reservation with Fuzzy Set Theory in Yogyakarta - Prihantini (Proceeding International Conference on Science and Engineering, 2021)
Abstract. In Indonesia, the soil conditions of each region are of course different, depending on the type of soil and the geographical location of a place or an area that affects the soil quality. For farmers, especially in the countryside, to understand the knowledge of good soil quality is difficult and it takes a long time to determine the right types of plants to plant in accordance with the soil. For that, it needs a strategy in knowing a polluted land or not especially for farmers. The purpose of this paper is to assist the process of dissemination of information and knowledge through calculations using fuzzy logic. In this research, the data that is processed is the land aspect data as a benchmark in determining whether or not soil contamination includes soil pH or soil acidity, soil minerals, soil structure and soil nutrients. At this writing is done fuzzy calculation analysis with Sugeno method. In this paper shows that the results obtained by the Sugeno method have results that are less in accordance with the actual data.